Factors Influencing Quality of Life in Elderly Stroke in Next Normal - ทรงไทย, ผศ.ดร.ณิชกานต์ (NU Journal of Nursing and Health Sciences, 2025)
The purpose of this cross-sectional research was to study factors predicting the quality of life of elderly people with stroke in the next normal era. The 120 elderlies with stroke diagnosed within six months, obtained from systematic random sampling was the study sample. Data were collected from profile files and structured interviews. The research tools were a demographic data and illness history form. The questionnaires consisting of 1) depression 2) perception of self-efficacy 3) social support and 4) quality of life of stroke patients. All four questionnaires have been previously completely standard content validity and reliability. The researcher asked permission to use it without modifying but re-test the reliability. The Cronbach's alpha coefficient of the questionnaire was obtained as 0.71, 0.94, 0.92, and 0.95, respectively. Data were analyzed by using descriptive statistics and analyze the binary logistic regression using the Forward stepwise method. The research results found that the elderly with stroke had an overall quality of life at a good level (70.8%). Factors which predict good quality of life include the severity of the disease, type of stroke, and perception of self-efficacy. The three factors together able to predict 61.9% with statistical significance at the .05 level and had a correct prediction efficiency of 87.5%. The results of this study can utilize to provide information for effective continuously care in order to promote good quality of life for elderly people with stroke.